Determinants of internet use by school-age children: The challenges for Mexico during the COVID-19 pandemic. (February 2022) - Martínez-Domínguez, Marlen; Fierros-González, Isael
Abstract: The COVID-19 pandemic has further highlighted the deep digital divide in Mexico and the enormous challenge faced by its education system in continuing to educate the country's students while under confinement. The objective of this article was to examine the determinants of internet acces s, use and productive uses for school-age children in households of different socioeconomic levels. The Heckman selection model was estimated based on data taken from the Encuesta Nacional sobre Disponibilidad y Uso de Tecnologías de la Información en los Hogares (ENDUTIH or National Survey on the Availability and Use of Information Technologies in the Household) 2018. The results obtained show that the probability of having children internet accessing and usage patterns (homework, courses, and blogs) depends on level of schooling, economic status, digital skills, and place of residence, as well as the presence of electronic devices and infomediaries in the household. These findings suggest the urgent need to redesign current ICT policy with a long-term integrated vision that guarantees access to ICTs and their productive use for students immersed in an ecosystem of educational innovation for the XXI century. Highlights: Mexican children use the Internet for recreational purposes and rarely in education. Income and educational level are essential in adoption and use of the Internet. The educational system must rethink the incorporation of the internet as a learning tool.